Kekuatan Tarik Sambungan Paku keling tunggal pada Komposit Polypropylene Hibrida Laminasi Serat Goni/Gelas - I.D.G Ary Subagia; A.H. Yuwono; I.G.A.K.C Adhi (Universitas Mataram, 2019)
This research is to investigate the tensile strength of hybrid composite with lamination of goni and glass fiber reinforced on single rivet joint. Four variant of gony and glass fiber lamination on single lap-joint by rivet were manufactured and the gony fiber reinforced polypropylene composite [g5] and glass fiber reinforced polypropylene composite [G5] also produced for control. The specimen was fabricated through hot-press on the temperature of 200 oC as long as 60 min. The strength of the rivet joint has been tested on tension machine with load 5000 (N) and crosshead speeds is 1 mm/min. The research purpose is to investigate the tension strength of riveted single lap-joint on hybrid composites based on the fibers laminate variation. The tension test result of each variation of hybrid composites shown as follow; The average value of tension strength of hybrid composite (H1) shows the high value is 10,179 MPa with elastic of modulus is 3,867 (MPa). Meanwhile, the average value of hybrid composite H2, H3, and H4 have tension strength relative similar i.e; 7,88 (MPa), 7,792 (MPa), and 7,84 (MPa) that positioned between the composites [G5] and [g5]. The laminate stacking of fibers is influencing of the strength and elastic of modulus of hybrid composites.